In vitro analysis of partially hydrolyzed guar gum fermentation differences between six individuals. Issue 4 (10th February 2016) - Carlson, Justin; Esparza, Julian; Swan, Jonathan; Taussig, David; Combs, Jerry; Slavin, Joanne
Abstract : Partially hydrolyzed guar gum (PHGG) is a fermentable, soluble, non-gelling fiber consumed as both a supplement and ingredient. Abstract : Partially hydrolyzed guar gum (PHGG) is a fermentable, soluble, non-gelling fiber consumed as both a supplement and ingredient. PHGG supports bifidogenic and lactogenic growth, and increases the concentration of short chain fatty acids (SCFAs) in the distal intestine due to its fermentability. Changes in SCFA development due to the fermentation of dietary fibers in the colon have been widely studied, but there are limited studies analyzing the differences in SCFA development across multiple individuals (ages 23–68) exposed to the same dietary fiber (PHGG). With the six donors analyzed in this study, gas production varied from 59–80 mL/0.5 g fiber at 12 h and 85–93 mL/0.5 g fiber at 24 h between the six donors. At 12 h butyrate concentrations varied from 6.99 μmol mL −1 to 23.84 μmol mL −1 and from 8.78 μmol mL −1 to 22.84 μmol mL −1 at 24 h. Total SCFA concentration at 24 h ranged from 42.85 μmol mL −1 to 91.17 μmol mL −1 . The overall average SCFA ratio for the six fecal donors was 30 : 45 : 25 (acetate : propionate : butyrate), which is similar to other fermentable fibers analyzed using in vitro systems. SCFA development in the distal intestine increases the amount of metabolizable energy from the diet, but varies greatly among people based primarily on the composition and changes of their gut microflora. With over a 2-fold difference in SCFA production, significant differences were found among healthy individuals fecal microflora when exposed to PHGG. Donor 6 SCFA concentrations decreased at 24 h, indicating a quicker fermentation process than the other five donors. All SCFAs measured fluctuated greatly among the six individuals within 24 h of analysis. Results of in vitro fermentation analyses are limited by the wide variation found with fecal donor.